2017
DOI: 10.1111/acer.13380
|View full text |Cite
|
Sign up to set email alerts
|

Does a Crossover Age Effect Exist for African American and Hispanic Binge Drinkers? Findings from the 2010 to 2013 National Study on Drug Use and Health

Abstract: Background Among general population studies, lower rates of binge drinking tend to be found among African Americans and Hispanics compared to Whites. However, among older adult populations, minority groups have been shown to be at higher risk for binge drinking, suggesting the presence of a crossover effect from low to high risk as a function of age. Aims To date, limited research has examined the crossover effect among African American and Hispanic populations compared to non-Hispanic Whites across large de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Prevention efforts must occur prior to the development of CUDs. This is critical for our sample, since these populations have the age crossover effect; that is, African Americans and Hispanic Americans appear to have a lower rate of substance use, but they catch up to European Americans with increasing age, and may surpass them later in life (Caraballo, Sharapova, & Asman, 2016; Watt, 2008; Zapolski, Baldwin, Banks, & Stump, 2017). Therefore, paying attention to substance use among African American and Puerto Rican adolescents may play an important role for prevention of CUDs in adulthood, even though little usage of substances occurs during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention efforts must occur prior to the development of CUDs. This is critical for our sample, since these populations have the age crossover effect; that is, African Americans and Hispanic Americans appear to have a lower rate of substance use, but they catch up to European Americans with increasing age, and may surpass them later in life (Caraballo, Sharapova, & Asman, 2016; Watt, 2008; Zapolski, Baldwin, Banks, & Stump, 2017). Therefore, paying attention to substance use among African American and Puerto Rican adolescents may play an important role for prevention of CUDs in adulthood, even though little usage of substances occurs during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, white people prefer to drink alcohol compared to Asians and Africans, and are more likely to be obese. 4,5 Furthermore, white people are more likely to have HCV and HBV co-infection, which can accelerate cirrhosis progression. [6][7][8] These phenomena may lead to a bias in the conclusion.…”
Section: Hepatocellular Carcinoma In the Absence Of Cirrhosis In Patimentioning
confidence: 99%
“…Taken with Vogt Yuan’s [6] differential findings between drug use and drug abuse , these data suggested that Blacks are more likely to experience problems from substance use in later adulthood despite consuming alcohol at similar frequencies to those of their White counterparts. However, recent research also suggests that the crossover in alcohol-and drug-related problems may be related to a crossover of heavy substance use during later adulthood by Blacks [19] (see “Emerging Focus on Heavy Drinking” section). Thus, research is needed that examines differences in potential crossover effects based on frequency and quantity of use, as well as problems from use across development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when stratifying by gender, the crossover for frequency of heavy drinking has been found for Hispanic men and Black women in the fourth decade [28, 29]. Conversely, a study stratifying by income found a crossover for likelihood of heavy drinking among only those Blacks earning less than $20,000 per year [19]. Finally, a study stratifying by generation (those born in 1962 versus those born in 1980) found a crossover for Blacks for heavy drinking among the older cohort by the early 30s, but only a convergence among the younger generation by that age [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation